Hoax-Free Movement: The Role of Inter-Institutional Communication in Asahan in the 2024 Election - Br Simbolon, Aznila; Rubino, Rubino; Ritonga, Elfi Yanti (Borong Newinera Publisher, 2024)
This research aims to examine the effectiveness of communication strategies in mitigating the spread of hoaxes during the 2024 Election in Asahan Regency. The research method used is a case study with a focus on collaboration between institutions such as the Communication and Information Service, Police, Bawaslu, KPU, and civil society organizations. Data was collected through in-depth interviews with representatives from each institution as well as analysis of related policy documents. Data analysis was carried out using a qualitative approach to identify effective communication strategies and the obstacles faced in their implementation. The research results show that coordinated collaboration between institutions is the key to tackling the spread of hoaxes. Communication strategies involving early detection, quick response to hoaxes, and digital literacy education campaigns have succeeded in mitigating the negative impact of hoaxes on the democratic process in Asahan Regency. This research contributes to strengthening election integrity, increasing public trust in democratic institutions, and building awareness of the importance of accurate information in political decision making.